Customary Land Rights and Postcolonial Land Governance: The Case of Pakel Village, Indonesia, 1950s-1980s - Nur Aini Setiawati; Purnawan Basundoro; Ardana Kusumawanto; Muhammad Agung Pramono Putro; Safrial Fachry Pratama (Paramita: Historical Studies Journal, 2025)
Abstract: This paper discusses the social practices and impacts of agrarian policy changes in Pakel Village, Licin District, Banyuwangi Regency. The existence of policy transformation has also changed the patterns of social life of the community, especially in the field of agricultural land ownership. This then triggered a land conflict involving the conflict actor, PT Bumi Sari, and the local community. This research uses qualitative research methods through an in-depth literature study approach. Theoretically, this paper illustrates that various conflicts are an important part of making agrarian policies, especially in areas where companies will build and in relation to community conditions. In the future, this will also contribute academically in the form of future research findings that look in more detail at the conditions of communities after conflicts through ethnographic studies. The results showed that the local community as the original entity in the area was marginalized due to the change in agrarian policy which then favored PT Bumi Sari. The existence of conflict is inseparable because of these differences of opinion and views, with a background as a farmer which makes the community marginalized from social construction, especially in agrarian affairs. However, the existence of these historical records makes lessons and evaluations together in every decision-making and policy determination that is fair and considers the local rights of indigenous people in the region. The discussion showed that land conflicts were related to the complexity and legal certainty that the Pakel Village community did not obtain. Restitution of customary land rights based on postcolonial legal pluralism is ignored, which can indirectly be understood as an attempt by the state to seize land from indigenous communities. Abstrak: Makalah ini membahas praktik sosial dan dampak perubahan kebijakan agraria di Desa Pakel, Kecamatan Licin, Kabupaten Banyuwangi. Adanya transformasi kebijakan juga telah mengubah pola kehidupan sosial masyarakat, terutama dalam bidang kepemilikan lahan pertanian. Hal ini kemudian memicu konflik lahan yang melibatkan pihak yang terlibat dalam konflik, PT Bumi Sari, dan masyarakat setempat. Penelitian ini menggunakan metode penelitian kualitatif melalui pendekatan studi literatur mendalam. Secara teoritis, makalah ini menggambarkan bahwa berbagai konflik merupakan bagian penting dalam pembentukan kebijakan agraria, terutama di daerah-daerah di mana perusahaan akan membangun dan terkait dengan kondisi masyarakat. Di masa depan, hal ini juga akan berkontribusi secara akademis dalam bentuk temuan penelitian masa depan yang meneliti lebih detail kondisi masyarakat setelah konflik melalui studi etnografi. Hasil penelitian menunjukkan bahwa masyarakat lokal sebagai entitas asli di wilayah tersebut terpinggirkan akibat perubahan kebijakan agraria yang kemudian menguntungkan PT Bumi Sari. Adanya konflik tidak terpisahkan karena perbedaan pendapat dan pandangan, dengan latar belakang sebagai petani yang membuat masyarakat terpinggirkan dari konstruksi sosial, terutama dalam urusan agraria. Namun, keberadaan catatan sejarah ini memberikan pelajaran dan evaluasi bersama dalam setiap pengambilan keputusan dan penetapan kebijakan yang adil serta mempertimbangkan hak-hak masyarakat adat di wilayah tersebut.